Pendampingan Pemasaran Tahu Putih “Bu Sipon” sebagai Upaya Meningkatkan Penjualan Melalui Marketplace Rekom Indonesia - Ulfa’ngin, Nadia; Amri, Muhtadin (Literasi Jurnal Pengabdian Masyarakat dan Inovasi, 2022)
Digitalization marketing is a solution to expand market share in an effort to increase sales turnover. Marketplace is an option that makes it easier for business actors in the online promotion process via the internet. The existence of the covid-19 pandemic that limits mobilization so that the method of getting around is no longer effective, so there needs to be improvements in marketing strategies. Through the ABCD (Asset Based Community Development) method, there are several stages carried out, namely; inculturation, discovery, design, define and reflection. The strategy used to increase sales turnover by using digital media through the marketplace is the best choice to achieve business goals. In the Online Community Service Lecture from Home (KPM-DDR) students of IAIN Ponorogo provide assistance in the marketing process. The end result of this service is the dedication of Mrs. Sipon's white tofu home industry with the Indonesian Rekom markerplace.